2022
DOI: 10.1515/jpm-2022-0310
|View full text |Cite
|
Sign up to set email alerts
|

Gestational complications associated with SARS-CoV-2 infection in pregnant women during 2020–2021: systematic review of longitudinal studies

Abstract: Objectives To identify gestational complications associated with SARS-CoV-2 infection in pregnant women during 2020–2021. Content The risk of gestational complications was confirmed during SARS-CoV and MERS-CoV infection. However, this is not robust for COVID-19 because there is still no scientific evidence from longitudinal studies. A systematic review was performed using four databases, and 14 prospective or retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…The observed association between COVID-19 infection during pregnancy and preterm birth is consistent with recent systematic reviews and meta-analyses. [3][4][5][6][7][8][9][10][11][12][13] Our results suggest, however, that the risk of preterm birth observed in prior studies may be driven by the preponderance of data on third-trimester COVID-19 infection 4,10,12 and may not be generalized to infection during the first and second trimesters. To the best of our knowledge, our study included one of the largest samples of first-trimester COVID-19 infection.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The observed association between COVID-19 infection during pregnancy and preterm birth is consistent with recent systematic reviews and meta-analyses. [3][4][5][6][7][8][9][10][11][12][13] Our results suggest, however, that the risk of preterm birth observed in prior studies may be driven by the preponderance of data on third-trimester COVID-19 infection 4,10,12 and may not be generalized to infection during the first and second trimesters. To the best of our knowledge, our study included one of the largest samples of first-trimester COVID-19 infection.…”
Section: Discussionmentioning
confidence: 72%
“…Preterm birth, defined as birth at <37 weeks of gestation, is the leading cause of neonatal death globally 1 and, together with low birthweight, the second leading cause of infant mortality in the United States. 2 According to recent systematic reviews and meta-analyses, [3][4][5][6][7][8][9][10][11][12][13] there is mounting evidence that COVID-19 infection during pregnancy is associated with an increased risk of preterm birth; however, data remain limited on the risk of preterm birth by trimester of infection. As a limitation of their review, Allotey et al 5 wrote: "Not many studies reported outcomes by trimester for symptom onset."…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that SARS-CoV-2 infection during pregnancy could be associated with preterm birth [ 32 ]. It was reported that newborns of mothers infected with SARS-CoV-2 were at an increased risk of preterm birth and admission to the Neonatal Intensive Care Unit [ 33 ]. Low birth weight and preterm birth were more likely to develop in pregnant women with COVID-19 than in those without COVID-19 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%